Insights into fluid evolution and Re enrichment by mineral micro-analysis and fluid inclusion constraints: Evidence from the Maronia Cu-Mo ± Re ± Au porphyry system in NE Greece - Jan J. Falkenberg; Manuel Keith; Vasilios Melfos; Max Hohl; Karsten M. Haase; Panagiotis Voudouris; Alica Höss; Julia Wenske; Reiner Klemd; Christoph Beier; Martin Kutzschbach; Harald Strauss (Mineralium Deposita, 2024)
Porphyry-epithermal veins hosting Re-rich molybdenite and rheniite (ReS 2 ) from the Maronia Cu-Mo ± Re ± Au porphyry in Thrace, NE Greece, provide new insights into the hydrothermal processes causing extreme Re enrichment. Quartz trace element chemistry (Al/Ti, Ge/Ti), Ti-in-quartz thermometry, and cathodoluminescence imaging reveal multiple quartz generations in consecutive hydrothermal quartz-sulfide veins associated with potassic, sericitic, and argillic alteration. Fluid inclusions in different quartz generations indicate that phase separation and fluid cooling are the main ore-forming processes in the porphyry stage (~ 500 – 350 °C), whereas mixing of a vapor-rich fluid with metalliferous (e.g., Pb, Zn, Au) meteoric water forms the epithermal veins (~ 280 °C). These processes are recorded by trace element ratios in pyrite that are sensitive to changes in fluid temperature (Se/Te), fluid salinity (As/Sb, Co/As), and mixing between fluids of magmatic and meteoric origin (Se/Ge). Highly variable intra-grain δ 34 S values in pyrite record S isotope fractionation during SO 2 disproportionation and phase separation, emphasizing the importance of in situ δ 34 S analysis to unravel ore-forming processes. High δ 34 S (~ 4.5‰) values of sulfides are indicative of low SO 4 2− /H 2 S fluid ratios buffered by the local host rocks and mixing of the magma-derived fluid with meteoric water. The formation of Re-rich molybdenite (~ 6600 ppm) is favored by cooling and reduction of a magma-derived, high-temperature (~400 °C), oxidized, and Re-rich fluid triggering efficient Re precipitation in early veins in the potassic alteration zone. The systematic temporal fluid evolution therefore reveals that coeval cooling and reduction of oxidized Re-rich fluids cause extreme Re enrichment at the Maronia porphyry system.

Trace element systematics of magnetite from the Starra iron oxide‑copper gold deposits reveals early fluid conditions characteristic for Cu mineralization - Max Hohl; Jeffrey A. Steadman; Jonathan Cloutier; Shaun L.L. Barker; Ivan Belousov; Karsten Goemann; David R. Cooke (Chemical Geology, 2024)